ANALISIS PERBANDINGAN APLIKASI PANDORA RECOVERY DAN RECUVA TERHADAP PENGEMBALIAN DATA WINDOWS - Pastima Simajuntak (UNIVERSITAS PELITA HARAPAN, 2017)
In completing a job, the use of computers has become absolutely necessary because at the time of this computerization has not only the function of the computer used to calculate. Processing data in the form of text, images or videos can be easily and quickly using a computer. But in reality, there are only events where the work, in the form of computer files, can be lost either so files that are needed are missing from the storage media in the computer. Because it returns the data that has been lost is essential to the work that has been done someone not in vain. In restore lost files, a lot of software that can be used, such as Pandora Recovery and Recuva. In the writing of this time will be discussed on the comparison between the two software. In the research that has been testing the test. It can be seen that the time left Recuva as Software better than Pandora Recovery. The possibility that an important factor why Recuva has been chosen by its users is way better than Pandora Recovery. Keywords: Pandora Recovery, Recuva, and Windows Data Recovery.